Pelaksanaan Handover Perawat dengan Komunikasi SBAR pada Pelayanan Keperawatan - Nasrianti Nasrianti; Mulyati Mulyati; Setiawati Setiawati; Mira Asmirajanti; Gunawan Irianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study explores the handover implementation of SBAR communication in the 2000 service in the Surgery Room of the Y Regional General Hospital, Papua Province. The research design uses an exploratory phenomenological approach with a purposive approach. The results of this study obtained five themes: nurses' knowledge, understanding, constraints, the benefits of SBAR communication, and nurses' experiences. After researching changes in doing handovers using SBAR communication, namely, the implementation of handovers can be done in a short time, decreasing the number of unexpected events, there is a new Standard Operating Procedure (SOP) based on the theory used. Before the research, the random incidence rate was 60.2%; after the study, the Unexpected Events (KTD) rate was 55.13%. Handover implementation time before the research was obtained with a duration of 25 minutes; then, after it was done, it became 19 minutes. In conclusion, five themes were found, namely nurses' knowledge, nurses' understanding, nurses' constraints, benefits of SBAR communication, and nurses' experiences. Keywords: Handover, SBAR Communication, Nurse